Pengembangan Penuntun Praktikum Berbasis Inkuiri Terbimbing Materi Interaksi Makhluk Hidup pada Siswa MTs Darul Amin Palangka Raya - Lidia Aprilia; Nanik Lestariningsih; Ayatusa'adah Ayatusa'adah (Universitas Veteran Bangun Nusantara Sukoharjo, 2020)
The aim of this research was to develop a practical guide based on guided inquiry on the interaction material of living things. This type of research was Research and Development with the ADDIE development model (Analyze, Design, Development, Implement and Evaluation). Practicum guides were validated by 2 media experts and 2 material experts. The research was carried out until a small scale test with the research subjects were 5 grade students of MTs Darul Amin Palangkaraya. The results of the study were a practical guide with 3 topics whose activities were designed according to the guided inquiry learning model. The practicum guide developed was declared feasible by material and media experts with a very valid category. Based on small-scale trials, the practicality value was produced with a percentage of 83.00% which was categorized as very good. These results showed that the practicum guide was declared valid and practical after a small-scale trial was carried out. The practicum guide still needs to be refined for further trials on a large scale